Coeliac disease in children with type 1 diabetes. (February 2018) - Kurppa, Kalle; Laitinen, Anna; Agardh, Daniel
Summary: Coeliac disease and type 1 diabetes are the most common paediatric autoimmune disorders. Both conditions have increasing incidence and can often coexist in a patient. The diseases share many genetic and immunological features, but diagnostic and treatment approaches vary substantially worldwide. Because of the often subtle presentation of coeliac disease in children with type 1 diabetes, many are diagnosed only upon screening for coeliac disease. In this Review, we summarise approaches to diagnosis and treatment of children with type 1 diabetes and coeliac disease, with a specific emphasis on those with a double diagnosis. In particular, we examine the pros and cons of screening for coeliac disease and assess the challenges of dietary treatment in children with coexisting type 1 diabetes, which can already be a burden. Furthermore, we present the latest research on the shared genetic and pathogenic mechanisms and introduce some future perspectives.